The Characteristic Function Property of Mixture Negative Binomial-Exponential Distribution - Dodi Devianto; Sarah Sarah; Siska Dwi Kumala; Maiyastri Maiyastri (Science and Technology Indonesia, 2018)
This paper introduces a new distribution by mixing the negative binomial distribution and exponential distribution namely negative binomial-exponential (NB-E) distribution. In is given the probability distribution function of NB-E distribution and its characteristic function by using Fourier-Stieltjes transform. In addition we present the some properties of characteristic function from NB-E distribution.